2007
DOI: 10.1093/jmedent/44.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Two Pyrethroid Insecticides Applied as Barrier Treatments for Managing Mosquito (Diptera: Culicidae) Populations in Suburban Residential Properties

Abstract: Increased threat of mosquito-borne disease coupled with decreased tolerance of nuisance mosquitoes has opened a market for pest management professionals to offer mosquito control services for homeowners. A pest management professional applied bifenthrin (0.08%) and lambda-cyhalothrin (0.1%) at their maximum label concentrations as barrier treatments. We tested treatments residual efficacy in reducing adult mosquito populations and compared these chemicals against a water control at 24 residential properties (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…The species of target mosquitoes can clearly affect the efÞcacy of treatment as demonstrated in laboratory (Pridgeon et al 2008, Cooperband and and Þeld studies (Groves et al 1997, Trout et al 2007). Behavioral studies on sublethal exposure to different pyrethroids demonstrated differences in ßight duration, velocity, turn angle, and angular velocity in three species of mosquitoes (Cohnstaedt and Allan 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The species of target mosquitoes can clearly affect the efÞcacy of treatment as demonstrated in laboratory (Pridgeon et al 2008, Cooperband and and Þeld studies (Groves et al 1997, Trout et al 2007). Behavioral studies on sublethal exposure to different pyrethroids demonstrated differences in ßight duration, velocity, turn angle, and angular velocity in three species of mosquitoes (Cohnstaedt and Allan 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of sand ßy habitat and presumed adult resting areas are central components to the management strategies described for many phlebotomines and mosquitoes (Perich et al 1993, Alexander et al 1995, Robert and Perich 1995, Hubbard et al 2005, Trout et al 2006, Trout et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…This species has been shown to potentially transmit at least 22 arboviruses, including dengue and chikungunya (Gratz 2004, Horwood et al 2013, and prefers resting on low, deeply shaded vegetation and leaf litter (Hawley 1988, Hubbard et al 2005, Lam et al 2010 in and around the community. This resting preference and suggestions from prior publications (Trout et al 2007, Li et al 2010) resulted in the adoption of harborage spray techniques by the Tropical Public Health Services. These treatments also are expected to provide additional beneÞt with the reduction of other foliage-resting mosquitoes near residential properties.…”
mentioning
confidence: 96%